Meynert’s Nucleus Complex White Matter Abnormalities in Autism Spectrum Disorders: An MRI Study - Pardini, Matteo; Garaci, Francesco G.; Zaborszky, Laszlo; Coniglione, Filadelfo; Serafini, Gianluca; Siracusano, Martina; Benassi, Francesca; Gialloreti, Leonardo Emberti (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Introduction: Cholinergic dysfunction has been proposed to play a role in autistic symtomatology. However, to date, its structural correlates are poorly understood. Methods: Twenty-five low-functioning, non-verbal males with Autism Spectrum Disorders (ASD) and 25 controls were enrolled in the study. All underwent MR T1-weighted 3D Structural Imaging and Diffusion Tensor Imaging. Grey and white matter components of the Meynert’s Nucleus Complex were then identified on MR images, and both grey matter density and white matter mean Fractional Anisotropy in the Meynert’s Nucleus region of interest were quantified for each subject. Non-verbal IQ was assessed in all subjects with ASD. Results: We showed reduced white matter Fractional Anisotropy in the bundles surrounding the Meynert’s Nucleus in ASD subjects compared to controls. Fractional Anisotropy in these bundles was positively associated with non-verbal IQ, independently from whole brain white matter mean Fractional Anisotropy. ASD subjects did not show significant abnormalities in Meynert’s Nucleus grey matter density. Conclusions: Our findings suggest that white matter abnormalities in the Meynert’s Nucleus might be involved in the cholinergic deficits of ASD.